Great as Queens, Kind as Mothers (Eurasian Scientific Herald, 2022)
This article is devoted to the country, mother, and nature used in the poetry of Zulfia, a brilliant artist, a munificent woman who can feel the reader's heart, a noble soul who is precious to her country, Motherland, a great woman of the East who carries a burden like a mountain on her shoulders. artistic comparisons are analyzed. At the same time, the poems of Aydin Khojieva, a contemporary Uzbek poetess with Zulfia, possessor of a sharp mind and heart, a motherly and beloved friend to her people, were analyzed in a comparative manner. In the article, we meet different types of poetic images